Parent recommendations to support physical activity for families with young children: Results of interviews in deprived and affluent communities in South Wales (United Kingdom). (2nd January 2020) - Khanom, Ashrafunnesa; Evans, Bridie Angela; Lynch, Rebecca; Marchant, Emily; Hill, Rebecca A.; Morgan, Kelly; Rapport, Frances; Lyons, Ronan A.; Brophy, Sinead
Abstract: Background: Physical inactivity is the fourth leading cause of mortality worldwide. Early childhood is a critical period when healthy behaviours can be instilled for a future active lifestyle. We explored community, societal and environmental factors affecting child and family physical activity and sought parent recommendations to support physical activity in families with young children. Methods: We interviewed 61 parents expecting a child or with a baby ≤12 months (35 mother and father paired interviews and 26 interviews with mothers only). We purposively sampled families for neighbourhood deprivation status (Townsend Index; 26 affluent; 35 deprived). We conducted thematic analysis of interview transcripts using Bronfenbrenner's socio‐ecological framework to guide interpretation. Results: We identified four themes: work family‐life balance; spaces for activity; beliefs and attitudes; and physical activity facilitators. We found that parents from deprived neighbourhoods were more likely to be underactive because of a complex web of community, social and personal factors which reduced motivation and hindered opportunity for physical activity. To increase knowledge and opportunity, respondents suggested 'help not tell' messages covering 'why', 'how' and 'where' information about physical activity, and using physical activity to support community engagement and social interaction. Conclusions: Recommendations from parents highlight effective communication about the importance of early child and family physical activity and improved community access to safe facilities and opportunities. Both parents need to be engaged in designing interventions to support greater physical activity and healthy behaviours which are relevant and achievable in individuals' lives.